Toward strong enforcement against improper marketing of personal information. New mission of the unsolicited marketing communication restriction in the era when security breach is inevitable - Keiko Kaneko (International Telecommunications Society (ITS), 2017)
Due to the development of technology and threats, personal information leakage is getting inevitable. In Japan, societal criticism and possible a large amount of economic loss occur to the entity having leaked personal information, but not so much against data broker purchasing the leaked information or entity buying it from them. To strengthen the restriction against the latter, the 2015 amendment of Act on the Protection of Personal Information (APIP) introduced the traceability and the on-site inspection authority by the Personal Information Protection Committee(PPC), but the authority can not conduct without clue that the personal information is in circulation. In the United States, there are monitoring services for important personal information which may lead economic damage or identity theft to the information subject, but in countries like Japan, where even basic information is accountable, monitoring for wider range of personal information is desired. Meanwhile, in the Do Not Call system introduced in 18 countries around the world, consumers can simply delete their information from the call list of the telemarketer only by registering their phone number with the National Registration. This is useful as a system to control consumers' personal information without imposing a burden of actively pursue specific entities using it by consumers. Here, I would like to propose a "Do not hold" system to delete personal information illegally acquired by enabling the authority to investigate it by which it gets possible to identify the entity having the information of the data subject.
Keywords: 330; personal information; data broaker; Do not call; the unsolicited marketing communication